Մեկնութիւն Մատթէի (Հատուածք) - Յովհան Ոսկեբերան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Каждое новое открытие армянского перевода V века вносит большой вклад в процесс изучения армянской традиции перевода Золотого Века. Таковы выявленные отрывки из 83, 84, 89 речей Иоанна Златоуста армянского перевода, которые содержат толкования на Евангелие от Матфея. Each new discovery of the 5th century Armenian translation has its major contribution to the process of completing the Armenian translation tradition of the Golden Age. These are the excerpts from 83, 84, 89 speeches of John Chrysostom of the Armenian translation, which contain comments from the Gospel of Matthew.
Keywords: Translation and interpretation; The Bible; Language and Literature